2017
DOI: 10.1002/bjs.10546
|View full text |Cite
|
Sign up to set email alerts
|

Tryptase expression as a prognostic marker in patients with resected gastric cancer

Abstract: Tryptase expression is an independent prognostic factor for overall and recurrence-free survival in patients with gastric cancer after surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Tumor immune signatures have provided enormous information regarding the status of tumor immune surveillance and the choice of immunotherapy [24][25][26]. By comparing the immunocytes infiltration between high and low IL17A groups, we revealed the fact that tumors with high IL17A mRNA and IL17A þ cells had higher antitumor mast cells [27], NK cells [28,29], and lower pro-tumor M2 [30] infiltration. These data suggested that IL17A þ cells in gastric cancer may function by influencing the infiltration of other immunocytes.…”
Section: Discussionmentioning
confidence: 91%
“…Tumor immune signatures have provided enormous information regarding the status of tumor immune surveillance and the choice of immunotherapy [24][25][26]. By comparing the immunocytes infiltration between high and low IL17A groups, we revealed the fact that tumors with high IL17A mRNA and IL17A þ cells had higher antitumor mast cells [27], NK cells [28,29], and lower pro-tumor M2 [30] infiltration. These data suggested that IL17A þ cells in gastric cancer may function by influencing the infiltration of other immunocytes.…”
Section: Discussionmentioning
confidence: 91%
“…Although most tumors evade immune surveillance at the time of presentation, the residual signs of active anticancer immune response present a favorable prognosis . High TIM density is associated with positive prognosis in some tumors . It is reported that TIM arrest the growth and induce apoptosis of breast cancer through secretion of IL‐4 .…”
Section: Discussionmentioning
confidence: 99%
“…9,20 High TIM density is associated with positive prognosis in some tumors. 10,13,21 It is reported that TIM arrest the growth and induce apoptosis of breast cancer through secretion of IL-4. 22 In the current study, we observed that TIM were positively correlated with prolonged OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations